Political economy analysis: Topic Guide - and Mcloughlin, Claire (GSDRC, University of Birmingham, 2014)
Political economy analysis (PEA) aims to situate development interventions within an understanding of the prevailing political and economic processes in society – specifically, the incentives, relationships, and distribution and contestation of power between different groups and individuals. Such an analysis can support more politically feasible and therefore more effective development strategies by setting realistic expectations …